Recent Advances in Aquaculture Systems Based on Microorganisms: The Biofloc Technology (Bft) Case - Coelho Emerenciano, Maurício Gustavo; Lemos de Mello, Giovanni; Silva Ribeiro, Felipe de Azevedo; Miranda-Baeza, Anselmo; Martínez-Córdova, Luis R. (Facultad de Ciencias Biologicas, 2015)
The demand for safety seafood is increasing globally year-by-year. On the other hand, the low productivity and recent diseases outbreaks lead the scientists to search for an alternative system to improve efficiently the aquaculture growth. Biofloc system, also called as biofloc technology (BFT), has the advantage to allow high production with limited or no water exchange. BFT has gained popularity because it offers a practical solution to maintain water quality and recycle feed nutrients. The continuous availability of natural food source in a form of microbial biomass lead the decrease of the feed conversion ratios and the possibility of employ alternative low protein diets, as well as alternative feed ingredients. More efforts have been done in penaeid shrimp nutrition as compared to fish nutrition under biofloc conditions.